Revealing the Impact of Different Iron‐Based Precursors on the 'Catalytic' Graphitization for Synthesis of Anode Materials for Lithium Ion Batteries. Issue 5 (21st February 2023) - Frankenstein, Lars; Glomb, Pascal; Ramirez‐Rico, Joaquin; Winter, Martin; Placke, Tobias; Gomez‐Martin, Aurora
Abstract: Invited for this issue's Front Cover is the group of Prof. Dr. Martin Winter from the MEET Battery Research Center (University of Münster, Germany). The cover picture shows two battery‐shaped coffee cups filled with coffee. In addition, the scientists (represented by gloved hands) have added both pure iron and an iron solution to the cups. The left cup filled with iron is highly energetic and strikes sparks, indicating better electrochemical performance and crystallinity than the right cup filled with the iron solution. The impact of activator addition prior to 'catalytic' graphitization and its effect on material and electrochemical properties is systematically investigated. Read the full text of the Research Article at 10.1002/celc.202201073 . Abstract :